Fluorescent Light Energy and Chronic Lesions: A Winning Association. Issue 7 (July 2021) - Crema, Alberto; Scarpa, Carlotta; Sonda, Regina; Rizzato, Sandro; Masciopinto, Giuseppe; Bassetto, Franco
Abstract : Background: Chronic ulcers represent a challenge for healthcare professionals and a large expense for national health care systems for their difficulty in achieving complete healing and for their high incidence of recurrence. With the progressive aging of the general population, the incidence of these injuries will only increase, further affecting the public health budget, hence the need to find new strategies for their management. The purpose of this study was to share the experience of the Complex Operational Unit of Plastic Surgery of the University Hospital of Padua with fluorescent light energy therapy, outlining its role in the treatment of chronic ulcers in the daily use outside the previous EUREKA study. Methods: In this case series study, we enrolled 15 patients with chronic ulcers of any etiology between January 2018 and July 2019 and we treated them using fluorescence light energy. We evaluated efficacy and safety endpoints reporting data in excel files completed by medical staff during the study. Results: The study confirms the effectiveness of fluorescent light energy inducing chronic ulcer healing, regardless of etiology, or at least preparing the lesions for a skin graft closure surgery. The system showed a low rate of complications established by patient adherence to treatment. Patients also reported a reduction in pain both at home and during outpatient dressings. Conclusion: Based on our experience, fluorescent light energy shows an excellent safety and efficacy profile in chronic ulcers no more responsive to traditional dressings and/or surgery.